“Confuso e intrincado labirinto”: fronteira, território e poder na Ilha Grande de Joanes (séculos XVII e XVIII) - DIAS, Joel Santos (Universidade Federal do Pará, 2017)
Marajó island or ilha Grande de Joanes had important role in the process of colonization of the Amazon. Its geographical position was considered strategic to ensure the safety and the supply of land located on the northern border, in addition to contributing directly and indirectly in the expansion of the border with the Spanish limits. Similarly, prominent role in the provision of genres and cattle to supply neighbouring areas, in particular, the State capital. The labor quota available was significant and removed for a long time the needs of the residents of the Crown itself, due to intense missionary activity developed with the Indians of that archipelago. In the period, the ancient villages Pombaline became towns and the indigenous peoples who lived there have been inserted in a new working relationship directed to ensure the continuity of its role. The resistance of the Indians of Brazil and its constant movement on the border.